Exploring the Neural Basis of Real-Life Joint Action: Measuring Brain Activation during Joint Table Setting with Functional Near-Infrared Spectroscopy - Egetemeir, Johanna; Stenneken, Prisca; Koehler, Saskia; Fallgatter, Andreas J.; Herrmann, Martin J. (Frontiers in Human Neuroscience, 2011)
Many every-day life situations require two or more individuals to execute actions together. Assessing brain activation during naturalistic tasks to uncover relevant processes underlying such real-life joint action situations has remained a methodological challenge. In the present study, we introduce a novel joint action paradigm that enables the assessment of brain activation during real-life joint action tasks using functional near-infrared spectroscopy (fNIRS). We monitored brain activation of participants who coordinated complex actions with a partner sitting opposite them. Participants performed table setting tasks, either alone (solo action) or in cooperation with a partner (joint action), or they observed the partner performing the task (action observation). Comparing joint action and solo action revealed stronger activation (higher [oxy-Hb]-concentration) during joint action in a number of areas. Among these were areas in the inferior parietal lobule (IPL) that additionally showed an overlap of activation during action observation and solo action. Areas with such a close link between action observation and action execution have been associated with action simulation processes. The magnitude of activation in these IPL areas also varied according to joint action type and its respective demand on action simulation. The results validate fNIRS as an imaging technique for exploring the functional correlates of interindividual action coordination in real-life settings and suggest that coordinating actions in real-life situations requires simulating the actions of the partner.